Biperiden Challenge Model in Healthy Elderly as Proof‐of‐Pharmacology Tool: A Randomized, Placebo‐Controlled Trial. (29th July 2021) - Bakker, Charlotte; van Esdonk, Michiel J.; Stuurman, Rik (F). E.; Borghans, Laura G.J.M.; de Kam, Marieke L.; van Gerven, Joop M.A.; Groeneveld, Geert Jan
Abstract: Selective M1 muscarinic acetylcholine receptor (mAChR) agonists are being developed as symptomatic treatment for neurodegenerative and neuropsychiatric disorders that lead to cognitive dysfunction. Demonstrating cognition‐enhancing effects in early‐phase clinical development in healthy subjects is difficult. A challenge with the M1 mAChR antagonist biperiden could be used to demonstrate procognitive and pharmacological effects of selective M1 mAChR agonists. The aim of this study was to develop such a model. To this end, 12 healthy elderly subjects participated in a randomized, placebo‐controlled, 3‐way crossover study investigating tolerability, pharmacokinetic (PK) and pharmacodynamic (PD) effects of 2 and 4 mg biperiden. Repeated PD assessments were performed using neurocognitive tasks and electrophysiological measurements. A population PK‐PD model was developed. Four milligrams of biperiden showed significant impairment of sustained attention (−2.1 percentage point in adaptive tracking [95%CI, −3.043 to −1.148], verbal memory (2‐3 fewer words recalled [95%CI, −5.9 to −0.2]) and working memory (up to a 50‐millisecond increase in the n‐back task reaction time [95%CI, 21.854‐77.882]) compared with placebo. The PK data were best fitted by a 2‐compartment model and showed high interoccasion and intersubject variability. Population PK‐PD analysis quantified significant concentration‐effect relationships for the n‐back reaction time, n‐back accuracy, and adaptive tracking. In conclusion, biperiden caused M1 mAChR‐related dose‐ and concentration‐dependent temporary declines in cognitive functioning. Therefore a biperiden pharmacological challenge model can be used for proof‐of‐pharmacology studies and to demonstrate cognition‐enhancing effects of new cholinergic compounds that are being developed.